2016
DOI: 10.1093/cvr/cvw174
|View full text |Cite
|
Sign up to set email alerts
|

Identifying circulating microRNAs as biomarkers of cardiovascular disease: a systematic review

Abstract: The aim of the present study is to identify microRNAs (miRs) with high potential to be used as biomarkers in plasma and/or serum to clinically diagnose, or provide accurate prognosis for survival in, patients with atherosclerosis, coronary artery disease, and acute coronary syndrome (ACS). A systematic search of published original research yielded a total of 72 studies. After review of the risk of bias of the published studies, according to Cochrane Collaboration and the QUADUAS Group standards, 19 studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
234
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(250 citation statements)
references
References 161 publications
(231 reference statements)
11
234
1
4
Order By: Relevance
“…verifying their utility for the early diagnosis of AMI (12). Despite all these achievements, it is essential to carry out clinical studies, including groups of individuals who have genetic differences that might influence miR expression.…”
Section: Plasma Levels Of Mir208b (A) and Mir499 (B) Were Significantmentioning
confidence: 99%
See 2 more Smart Citations
“…verifying their utility for the early diagnosis of AMI (12). Despite all these achievements, it is essential to carry out clinical studies, including groups of individuals who have genetic differences that might influence miR expression.…”
Section: Plasma Levels Of Mir208b (A) and Mir499 (B) Were Significantmentioning
confidence: 99%
“…In contrast, the levels of circulating plasma miRs can be measured rapidly using realtime PCR, offering two main advantages over standard antibody-based assays: increased sensitivity and specificity. Several studies have already considered circulating cardiacspecific or -enriched miRs as new biomarkers for the early diagnosis of AMI (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, abrogation of Nos3 promoter DNA methylation increases basal eNOS mRNA expression in vitro and protects against hind limb ischemia injury in vivo [75]. Similarly, growing evidence suggests a central role of miRNAs in the genesis of cardiometabolic dysfunction, also proposed as sensitive molecular markers of vascular disease [76]. In fact, we recently reported that circulating levels of miRNA Let-7 and miR-126 are associated with different traits of cardiometabolic dysfunction in children as well as have a predictive value for metabolic syndrome in these subjects [77].…”
Section: Epigenetics and Endothelial Dysfunctionmentioning
confidence: 99%
“…Furthermore the promising role of miR-1 (3 studies) in the diagnosis of acute coronary syndromes and the regulation of miR-145 in STEMI patients is highlighted. A meta-analysis, however, is not presented because of heterogeneous study designs and analytical reasons (1).…”
Section: Recently Navickas Et Al Published a Review On The Role Of Mmentioning
confidence: 99%